Clean delivery kit use in low-and middle-income countries: a systematic review and meta-analysis - Natnael Atnafu Gebeyehu; Yibeltal Assefa Atalay; Kirubel Dagnaw Tegegne; Gebeyaw Biset; Kelemu Abebe Gelaw (BMC Pregnancy and Childbirth)
Abstract Background The use of Clean Delivery Kits (CDKs) promotes healthy birth outcome. Nevertheless, representative data are lacking for low- and middle-income countries. Thus, study aimed at determining the overall estimate of clean delivery kit use among low and middle income countries. Methods A comprehensive review of the Science Direct, Scopus, Google Scholar, EMBASE, and PubMed databases was part of the current investigation. Microsoft Excel (version 14) was used to extract the data, and STATA statistical software was used for analysis. The presence of publication bias was assessed using DOI Plots in the study. By calculating I2 and doing an overall estimation analysis, heterogeneity was evaluated. Furthermore, a subgroup analysis was carried out according to the sample size, publication year, and study design. Results Out of 654 articles, 12 met the inclusion criteria and were included in the analysis, covering 19,889 study participants. In low- and middle-income countries, the pooled proportion of clean delivery kits use was 54% (95%CI: 31. 60, 76.82, I2 = 70%). Notably, the cross-sectional study revealed the lowest incidence of delivery kit use, with a proportion of 54.29%, while the cohort study revealed the highest proportion, at 72.37%. In studies with sample sizes < 500, clean delivery kit use was higher (60.28%) compared to studies with sample sizes > 500 (45.75%). Lastly, the proportion of clean delivery kits was found to be 62.53% for studies published after 2010, compared to 48.25% for studies published before 2010. Conclusion In summary, the proportion of clean delivery kits use was 54%. Healthcare systems should focus on different strategies to improve clean delivery kit use.